SUPERVISI KARYAWAN ROOM BOY SECTION PADA HOUSEKEEPING DEPARTMENT HOTEL FAVE PEKANBARU - Asmawi, Rada; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Supervision is the way of company to inprove the quality of employess work result. This research aimed to describe the application of supervisory task of the housekeeping department at Fave Hotel Pekanbaru. Related to supervision and performance avaluation and coordinate work for employees. Supervisor must strive to maintainthe stability of employees relations within management so as to create a conducive environment and also the communication with employees. In this research uses a qualitative method. Data was collected by using observation, interviews, and documentation. Here the researcher conducted an inteview with a housekeeping supervisor. The results show that the supervisory at Fave Hotel Pekanbaru is fair on the division of work tasks. And it can be concluded that supervisor must be able to provide good examples of their employees and able to solve a problem quickly and accurately.Key words : Supervision, Coordination, Evaluation, Briefing